ANALISIS KEJADIAN INFEKSI SALURAN KEMIH BERDASARKAN PENYEBAB PADA PASIEN DI POLIKLINIK UROLOGI RSUD DR. M. YUNUS BENGKULU - liza fitri lina; Dwi Puji Lestari (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2019)
Â Urinary infection is a pathological condition that has been known for a long time and can be found in various primary health services to subspecialty. The purpose of this study was to analyze the incidence of infection urinary tract in patients at the urological clinic poly Dr. M Yunus Bengkulu. The research design used qualitative with a descriptive approach. The informant's research method in this study used the